2013
DOI: 10.1186/1752-153x-7-20
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular H-bonding interaction in angular 3-π-EWG substituted imidazo[1,2-a]pyridines contributes to conformational preference

Abstract: BackgroundThe proton at position 5 of imidazo[1,2-a]pyridines substituted with an angular electron withdrawing group (EWG) at position 3, shows an unusual downfield chemical shift, which is usually explained in terms of a peri effect. However usage of this term is sometimes confusing. In this investigation, it is proposed that the aforementioned shift is in fact a combination of several factors: Anisotropy, long-distance mesomerism and an attractive intramolecular interaction of the electrostatic hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The interaction energies of polar hydrogen-π interactions are much stronger than that of nonpolar hydrogen-π interactions (CH-π), comparable or even larger than common hydrogen bonds. In this study the notation Hp-π is used for the polar hydrogen-π interactions, to make difference from the nonpolar hydrogen-π interactions (H-π or CH-π), and the common hydrogen bond interactions (H-b) [21-25]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction energies of polar hydrogen-π interactions are much stronger than that of nonpolar hydrogen-π interactions (CH-π), comparable or even larger than common hydrogen bonds. In this study the notation Hp-π is used for the polar hydrogen-π interactions, to make difference from the nonpolar hydrogen-π interactions (H-π or CH-π), and the common hydrogen bond interactions (H-b) [21-25]. …”
Section: Introductionmentioning
confidence: 99%
“…The Hp-π interactions are a unique interaction type that cannot be classified into other molecular interaction types, such as common hydrogen bond [21-25], cation-π interaction [26-29], electrostatic interaction, and van der Waals interaction. The physical nature and the interaction strength of Hp-π interactions are often a debatable topic.…”
Section: Introductionmentioning
confidence: 99%
“…44 65.07 2g 63.17HURZOL 45 65.16RELQUW 46 64.98 2h 64.74KABMIM 47 66.21RUJNEQ. 48 64.61 2i 63.81MIXZOJ 49 65.44TIDVIN 50 66.07 2j 64.63MIXZUP 51 67.52TUZYEU 52 65.44 2k 65.36MONREO 53 66.12UTITEX 54 62.07 2l 67.34NAGGEH 55 65.27VEGKAU 56 64.34 2m 60.69NAGGEH01 57 64.84WUHKER 58 62.24 2n 62.87NOGRIM 59 65.44YEDHIY 60 63.06 2o 66.69NONFOM 61 64.30ZUNVOV 62 68.57AHOMIV 63 63.75NONFOM01 61 65.95ZUPCOE 62 66.04BEGTUE 64 62.92NUBVUD 65 63.87ZUSSAJ 66 63.31CAJTIQ 67 67.82NUBWAK 65 64.00…”
Section: Resultsmentioning
confidence: 99%
“…To exclude a misleading crystal packing effect, we carried out a quantum chemical modeling of both conformations of the rac -Ir5-TfO cation in the absence of crystal effects at the PBE0-D3/IMCP-SR1 , //PBE0-D3/SBKJC SMD­(butanol) level of theory (full computational details in SI). These calculations revealed that conformer A is indeed 5.3 kcal·mol –1 lower in energy than B, which affirms that conformer A is clearly preferred in solution as well . Having ruled out excessive conformational freedom of the N -bound acyl group, we were now able to shed light on the underlying manner of chiral recognition of intermediates of type Λ-Ir5-Int by the addition of a molecular surface to the complex cation of intermediate analog Λ-Ir5-TfO (Figure ).…”
Section: Resultsmentioning
confidence: 99%